ANALISIS PENGARUH ANNUAL REPORT AWARD (ARA) PADA PERUSAHAAN YANG MENERAPKAN PRINSIP GOOD CORPORATE GOVERNANCE (Kasus Pada Perusahaan yang Terdaftar di BEJ) - Setiyono, Setiyono; Yuliawati, Eriyana (Jurnal Analisis Bisnis Ekonomi, 2006)
Intention of this research is to analyse the market reaction to announcement of Annual Report Award (ARA) and know the announcement influence to return of company of FIG receiver. Population in this research 7 company of receiver of year FIG 2002 and 2003 enlisted Effect Exchange Jakarta. This research test the market reaction by using analysis of event study utilize to analyse the market reaction and to see yhe information content. Its result prove that by signifikan the market response announcement, this matter reflection of society bilief to concept of corporate governance which base on the appreciatoon. For the examination of abnormal difference return used t test by using analysis of compaire mean, what intended to know the FIG influence to return of the appreation receiver company. Its result assess the profitabilitas before and at the (time) of announcement here after and at the time of announcement bigger than 0,05 so that no abnormal mean difference return among both. Matter this means that FIG announcement not have an effect on to return of the appreciation receiver company.